2021
DOI: 10.1108/ijoa-09-2020-2423
|View full text |Cite
|
Sign up to set email alerts
|

Fluffy PR and ‘comms girls’: banter, social interactions and the office culture in public relations in England

Abstract: Purpose The purpose of this paper was to explore social interactions, banter and the office culture in the public relations (PR) industry in England with the use of the difference approach and Bourdieu’s habitus theory. The paper explores whether PR organisations act as masculine habitus. Design/methodology/approach Qualitative interviews were conducted with 26 women practitioners, and thematic analysis was used to analyse data. Women were asked questions on social interactions, banter and the office culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…In addition to the office interactions and banter, de-patriarchalisation of PR is evident regarding the dress code, which echoes similar findings from a recent study conducted in England (Topić, 2020, 2021). A few interviewees stated that there is a “prescribed code of conduct which includes the dress code – business style of dressing” (interviewee 1), “yes, we have dress code, it's called smart casual.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to the office interactions and banter, de-patriarchalisation of PR is evident regarding the dress code, which echoes similar findings from a recent study conducted in England (Topić, 2020, 2021). A few interviewees stated that there is a “prescribed code of conduct which includes the dress code – business style of dressing” (interviewee 1), “yes, we have dress code, it's called smart casual.…”
Section: Resultssupporting
confidence: 86%
“…Moreover, all interviewees agreed that networking is extremely important for two reasons – career advancement and job requirement in the PR industry which is similar to the findings in England where women as well reported that networking is a job requirement (Topić, 2020, 2021). This view is echoed by interviewees from this study,Every time we organise or go to the events we have to network, mingle and share our visit cards in order to acquire new clients.…”
Section: Resultssupporting
confidence: 76%
“…The communications/PR literature points to several reasons holding women back from the promotion (breaking through the glass ceiling) to senior leadership positions within the PR industry (See, for example, Fielden et al. , 2003; Place and Vardeman-Winter, 2018; Polić and Holy, 2021; Topić, 2021; Topić, 2020; Topić et al. , 2019; Yeomans, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and empirical research have faithfully reflected the growth of women working in communication management and public relations (Aldoory and Toth, 2002; Dubrowski et al. , 2019; Topić, 2021a). However, the third wave of feminism highlighted the unfavourable position of women concerning men due to patriarchy and gender-related social, political and economic inequalities in organisations and society (Pompper, 2007).…”
Section: Introductionmentioning
confidence: 99%